2018
DOI: 10.29029/busbed.378121
|View full text |Cite
|
Sign up to set email alerts
|

Examining Coping Strategies In Accordance With Perceived Social Support

Abstract: Öz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…For example, conducted a study on African and American adolescents and found that social support was associated with adolescents' coping skills, and adolescents with good social support also had good coping skills. Bedel and Kutlu (2018) found that perceived social support in Turkish secondary school students positively predicted active coping and negatively predicted avoidant coping. Bal et al (2003) found that social support positively affects well-being and coping with stressful events in adolescents aged 12-18 years.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, conducted a study on African and American adolescents and found that social support was associated with adolescents' coping skills, and adolescents with good social support also had good coping skills. Bedel and Kutlu (2018) found that perceived social support in Turkish secondary school students positively predicted active coping and negatively predicted avoidant coping. Bal et al (2003) found that social support positively affects well-being and coping with stressful events in adolescents aged 12-18 years.…”
Section: Discussionmentioning
confidence: 94%
“…It is stated in the literature that there are three dimensions of coping: active, avoidant, and negative . While active coping is a constructive coping strategy to solve the problem with a positive approach, an avoidant coping strategy is to wait for the solution from different places instead of focusing on the problem, while negative coping believes that it cannot solve the problem and blaming people for the problem (Bedel & Kutlu, 2018;. ).…”
Section: Introductionmentioning
confidence: 99%
“…Öğrencilerin annesinden, babasından, öğretmeninden, yakın arkadaşlarından ve sınıf arkadaşlarından aldıkları sosyal destek arttıkça daha çok problem çözme eğilimine girdikleri sonucuna varılmıştır. Literatürdeki bazı araştırma sonuçlarının da bunu desteklediğini görmekteyiz (Korkut, 2002;Bedel ve Kutlu, 2018).…”
Section: Bulgularunclassified
“…Bedel ve Kutlu'nun yaptığı araştırma sonucuna göre ise ergenlerin aldıkları sosyal destek arttıkça kaçınma stratejisi yerine aktif başa çıkma stratejisini kullanmaları da artmaktadır(Bedel ve Kutlu 2018).Stresle Başa Çıkma Ölçeği toplam puanları ile Çocuk Ergen Sosyal Destek Ölçeği ''Önem'' boyutu toplam puanları arasında pozitif yönlü anlamlı ilişki görülmektedir. Bu durum bize öğrencilerin, aldıkları sosyal desteğe verdikleri önemin arttıkça stresle başa çıkmalarının da arttığını düşündürebilir.…”
unclassified